Carbon Footprint Cost Index: A Pavement Case Study. (2015) - Mosier, R.D.; Gransberg, D.D.
Abstract: Public projects for pavement and pavement maintenance are often based on budgets set by capital improvement budgets. A better way for determining the cost of sustainability in infrastructure costs is needed. The capitol budget limitation causes an issue for the owner. The municipality must construct projects with a focus solely on initial cost and cannot include sustainability requirements due to the perceived additional cost. Sustainability can often be viewed as subjective. Utilizing the carbon footprint as the basis for the decision creates a much more objective evaluation of sustainability in pavements. A case study illustrating a carbon footprint cost index is presented.